Diffusion of Nb in Fe and Fe alloys - Kurokawa, Susana; Ruzzante, José Evaristo; Hey, Alfredo Martín; Dyment, Fanny (The Metals Society, 1983)
Fil: Kurokawa, Susana Comisión Nacional de Energía Atómica; Argentina